Ph.D. partnership: effective doctoral supervision using a coaching stance. Issue 3 (16th March 2022) - Wilson, Jay; James, Wendy
ABSTRACT: Interactions between a graduate student and their supervisor are the backbone of a successful doctoral experience. Although the number of doctoral students is increasing, there are fewer full-time doctoral students. The emerging part-time student segment represents a unique trend in higher education, creating greater diversity than traditional full-time students on an academic track. The shift impacts and complicates the student's overall experience in developing and sustaining relationships with their supervisor. Traditional mentorship models suggest progressing through doctoral studies in a manner that may be inappropriate for this new group of part-time, professional Ph.D. candidates. This study applies an autoethnographic approach in examining how a coaching stance supports a faculty/student relationship. The paper shares two sides of the journey and the resulting reflections. The outcomes represent the supervisor and student experience and surface critical aspects of the relationship and the associated dissertation writing process. The result is a detailing of a unique experience and the lessons drawn from it. These lessons provide guidance in working with doctoral students in a more supportive and productive manner. Recommendations include using coaching questions, fostering increased student responsibility for their studies, and methods to make the supervision process intentionally purposeful.